Adoption Entrepreneurial Ecosystem Business Based on Integral Ecology To Achieve Sustainable Resilience - Pranatasari, Fransisca Desiana; Diva, Maria Angela (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Organizations must survive competitive competition. The fluctuating dynamics of the business world trigger organizations to adapt to changes. Integral ecology is an integrative model that connects the balance of business management with economic, environmental, social, and cultural ecology. Integral ecology is believed to be a pattern of interaction between living things and their habitats to achieve a sustainable balance.Purpose: This study analyzes activities and identifies integral aspects of an ecologically based entrepreneurial ecosystem in a business organization (business actors/community). This study also formulates patterns of adaptation and adoption of business organizations to support improving business quality. This study serves as a reference for achieving sustainable resilience.Design/methodology/approach: A qualitative approach with data validity through triangulation of sources and techniques.Findings/Result: This research finding integrative model that connects the balance of business management with economic, environmental and social ecology along with cultural ecology. Conclusion: The formulation of this pattern is a recommendation for an integral ecology-based entrepreneurship ecosystem model to achieve sustainable resilience, which can be adopted to improve the quality of businesses that are sensitive to the environment.Originality/value (State of the art): This study focuses on businesses that have implemented triple bottom line practices by paying attention to environmental aspects. Businesses with good practices are believed to achieve sustainability through resilience and sustainability principles. Efforts to align economic development with environmental sustainability are very important in various fieldsKeywords:   business organization, entrepreneurial ecosystems, integral ecology, sustainable resilience, business management